Comparison of extracorporal shock wave pretreatment to classic surgical delay in a random pattern skin flap model - Reichenberger, Matthias; Keil, Holger; Müller, Wolf; Herold-Mende, Christel; Gebhard, Martha Maria; Germann, Günter; Engel, Holger (Plastic and reconstructive surgery, 2011)
Background: - Extracorporal shock wave therapy has a significant positive effect on rescuing the ischemic zone of flap tissue if applied immediately after surgical intervention. The purpose of this study was to determine the potential preoperative effect of noninvasive extracorporal shock wave therapy to precondition flap tissue compared with the well-established surgical delay procedure. - Methods: - Thirty-two male Wistar rats were randomized into four groups, and an oversized, random-pattern flap was raised in each animal. In group D7, a surgical delay was carried out 1 week before full flap harvest. In group E7, the whole flap area was treated with extracorporal shock wave therapy to induce mechanical delay. Group E7D7 was treated preoperatively with a combination of surgical delay and extracorporal shock wave therapy. Group C constituted the control group, in which the skin flap was harvested without any prior intervention. Seven days after flap harvest, flap survival, perfusion, microvessel density, and vascular endothelial growth factor concentration were assessed. - Results: - Flap survival, perfusion, and microvessel density were significantly increased in the delay group (group D7) and the extracorporal shock wave therapy group (group E7) compared with the control group (group C). Combining both pretreatments (group E7D7) did not have a favorable cumulative effect. Vascular endothelial growth factor expression was not significantly increased in any group. - Conclusions: - Although not superior to surgical delay, the authors see many advantages of extracorporal shock wave therapy; it is noninvasive, easily applicable, less time- consuming, and less expensive. Thus, it may constitute an alternative procedure in clinical situations that warrant a noninvasive, fast, and easily applicable treatment.
Gesehen am 14.09.2022